Exploring the role of the church in sustainable development : a case study of the relief and Development Department of the Church of Church of Central Africa Presbyterian (CCAP) Nkhoma Synod - Saka, Arnold Kalemba (Stellenbosch : Stellenbosch University, 2025)
Thesis (MTh)--Stellenbosch University, 1974.